Analisis perceived enjoyment sebagai variabel anteseden technology acceptance model - Meilan Sugiarto; Retno Widuri (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2017)
Background: Young people are active users of the information technology, especially internet. Even some of them tend to make the internet as a medium of the main support for daily activities. This study indicates that internet use among young people, especially college student tends to have a model of its own behavior, making it attractive for further investigation. Purpose: This study focuses on the influence of perceived enjoyment as antecedent variable in the technology acceptance model (TAM). Methodology: The respondents of this study were college students as internet users in Yogyakarta, the province is considering a student city. This study was conducted on 130 respondents. Findings: According to the structural analysis with SEM method, shows that perceive enjoyment has a role as antecedent variable on TAM, because that variable has significant effects on variables in technology acceptance model. Keywords: perceived enjoyment, technology acceptance model, internet user, college student.